Vitamin D metabolites are associated with clinical and MRI outcomes in multiple sclerosis patients. Issue 2 (3rd November 2010) - Weinstock-Guttman, Bianca; Zivadinov, Robert; Qu, Jun; Cookfair, Diane; Duan, Xiaotao; Bang, Eunjin; Bergsland, Niels; Hussein, Sara; Cherneva, Mariya; Willis, Laura; Heininen-Brown, Mari; Ramanathan, Murali
Abstract : Purpose: The associations between vitamin D and MRI measures of brain tissue injury have not been previously investigated in multiple sclerosis (MS). This research evaluates the significance of vitamin D and its active metabolites in brain tissue injury and clinical disability in MS patients. Methods: The study population consisted of 193 MS patients (152 women and 41 men; mean age 46.1 (SD 8.4) years; disease duration 13.8 (SD 8.4) years). Serum levels of 25-hydroxyvitamin D3 (25(OH)VD3 ), 25-hydroxyvitamin D2 (25(OH)VD2 ), 1α, 25-dihydroxyvitamin D3 (1, 25(OH)2 VD3 ) and 24( R ), 25-dihydroxyvitamin D3 (24, 25(OH)2 VD3 ) were measured using a novel capillary liquid–chromatography–mass spectrometry method. Disability was assessed with the Expanded Disability Status Scale (EDSS) and the MS Severity Scale (MSSS). MRI measures included T2 lesion volume (LV), T1-LV and brain parenchymal fraction. The associations between deseasonalised levels of vitamin D metabolites and clinical and MRI measurements were assessed using regression analyses. Results: Lower deseasonalised levels of total 25(OH)VD (p=0.029), 25(OH)VD3 (p=0.032) and 24, 25(OH)2 VD3 (p=0.005) were associated with higher MSSS. Similarly, lower deseasonalised levels of 24, 25(OH)2 VD3 (p=0.012) were associated with higher EDSS. Higher values of the 25(OH)VD3 to 24, 25(OH)2 VD3 ratio were associated with higher MSSS (p=0.041) and lower brain parenchymal fraction (p=0.008). Conclusions: Vitamin D metabolites have protective associations with disability and brain atrophy in MS. In particular, the results indicate strong associations for the 24, 25(OH)2 VD3 metabolite, which has not been extensively investigated in MS patients.